EFEKTIFITAS PEMBERIAN TOPIKAL ASI DIBANDING PERAWATAN KERING TERHADAP KECEPATAN WAKTU LEPAS TALI PUSAT DI PUSKESMAS SUMBERSARI JEMBER - Eni Subiastutik (Jurnal Ilmu Kesehatan Masyarakat, 2012)
One of high infant mortality rate causes in developing countries is umbilical cord infection. Umbilical cord is a bacterial colony site that can cause infection in newborns such as omphalitis and sepsis. Umbilical cord care with topical breastmilk which contains anti-infection and anti-inflammation can speed up time of umbilical cord separation and prevent infection in neonatal period. Objective;to find out effect of topical breastmilk administration compared to dry care toward time of umbilical cord separation. Method;this was a clinical trial study with randomized clinical trial design. Subjects were all newly born babies that met inclusion criteria in Sumbersari inpatient community health center of Jember. Sample size was 64 babies divided into two groups, namely treated group consisting of 32 babies and control group consisting of 32 babies as well. Randomization was done with random technique of block 6 allocation. Data were analyzed using bivariate analysis with independent t-test and multivariate analysis with linear regression, with CI 95% and p< 0.05. Result;There was a mean difference in time of umbelical cord separation with topical breastmilk which was shorter (5.69 days) than with dry care (7.06 days), with coefficient value of -1.37 and p=0.000. Result of multivariate analysis showed that there was a significant relationship between umbilical cord care and umbilical cord separation with incidence of local infection, with coefficient value of -2.11 and R2 0.67(67 %). Conclusion;In time of umbilical cord separation in which treatment with topical breastmilk was shorter than that with dry care.   Keywords: topical breastmilk, dry care, time of umbilical cord separation